Metal-doped spinel catalyst for water electrolysis of CD-ROM drive and preparation method of metal-doped spinel catalyst
Patent Information
- Application Number
- CN202411389984.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-07
AI Technical Summary
IrO2是酸性水分解中阳极氧化最稳定的催化剂,具有优异的抗酸腐蚀性和抗高电位氧化性,但极其稀缺的资源和高昂的价格使得该项技术无法产业化应用
[0020]本发明提供的用于光驱水电解的金属掺杂尖晶石催化剂,为变价的d区金属掺杂的MnXCo3-XO4;本发明制备的M-MnXCo3-XO4材料具有优异的耐酸介质腐蚀性,实现了高催化活性和持久的耐久性,构筑的光伏驱动酸性水电解实现了超过20%的光至氢燃料的转换效率。而且本发明制备工艺操作简单,反应条件温和,大幅降低了催化剂应用的产业工业化成本。
Smart Images

Figure CN119265618A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalytic nanomaterials, and in particular to a metal-doped spinel catalyst for light-driven water electrolysis and a preparation method thereof. Background Art
[0002] Hydrogen fuel has high calorific value (143MJ Kg -1 ) and zero carbon pollution, it is currently the most promising energy carrier, which is expected to reduce or even get rid of dependence on traditional fossil energy and innovate the current energy structure. Depending on whether there is carbon emission in the process of hydrogen fuel source, it can be divided into "gray hydrogen", "blue hydrogen" and "green hydrogen". At present, more than 98% of hydrogen fuel in the world is "gray hydrogen" and "blue hydrogen", that is, hydrogen produced from coal, natural gas and chemical petroleum, which leads to a large amount of carbon emissions. Although hydrogen produced by water electrolysis has zero carbon emissions, that is, "green hydrogen", if grid electricity is used, the cost of hydrogen production is high, which limits its large-scale application in the industry. Photovoltaic-driven water electrolysis hydrogen production is photovoltaic-powered, which can realize distributed hydrogen production and absorb a large amount of renewable energy.
[0003] Photovoltaic-driven water electrolysis hydrogen production technology, photovoltaic (PV) materials and electrocatalyst materials are the two major limiting factors that restrict hydrogen production efficiency. At present, PV technology is approaching maturity and has achieved large-scale commercial application, so high-efficiency and durable electrocatalysts in acidic systems have become the main limiting factors. IrO2 is the most stable catalyst for anodic oxidation in acidic water decomposition, with excellent acid corrosion resistance and high potential oxidation resistance, but extremely scarce resources and high prices make this technology impossible to apply industrially. This requires us to develop water electrolysis catalysts suitable for photovoltaic-driven acid-resistant media, which have both low prices and long-lasting long-cycle durability.
[0004] Spinel materials are the most excellent acid corrosion-resistant materials among non-precious metal oxides, and can be used for high-potential anode water oxidation in acidic media. The spinel structure contains octahedral sites and tetrahedral sites, of which the octahedral sites are active catalytic sites and the tetrahedral sites are inert catalytic sites, which makes the overall catalytic activity of spinel materials average. Activating the inert tetrahedral sites will enhance the catalytic activity of spinel. Constructing metal-doped spinel catalysts can achieve durability in acid media at high potentials while improving anode water oxidation activity and achieving high light-to-hydrogen fuel conversion efficiency. Summary of the invention
[0005] In view of this, the present invention proposes a metal-doped spinel catalyst for light-driven water electrolysis and a preparation method thereof. The electrocatalyst of the present invention has high catalytic activity and durability in acidic media, and the preparation process is simple, easy to operate, and has good repeatability, which can significantly reduce the cost of the catalyst.
[0006] The technical solution of the present invention is implemented as follows: The present invention provides a metal-doped spinel catalyst for light-driven water electrolysis, the catalyst uses spinel material as a substrate, and the doped metal is a d-block transition metal.
[0007] In some embodiments, the spinel material includes at least one of MnCo2O4, CoMn2O4, Co3O4, and Mn3O4.
[0008] In some embodiments, the doping metal includes at least one of Ti, V, Nb, and Ta.
[0009] In some embodiments, the doping molar ratio of the doping metal is 2.5%-10%.
[0010] In a second aspect, the present invention further provides a method for preparing the metal-doped spinel catalyst for light-driven water electrolysis, comprising the following steps:
[0011] (1) mixing a spinel precursor compound and a doping metal compound to prepare an aqueous solution, and subjecting the mixture to ultrasonic treatment, wherein the spinel precursor compound comprises at least one of a manganese-containing compound and a cobalt-containing compound;
[0012] (2) mixing the mixed solution after ultrasonic treatment in step (1) with the Nafion solution and then ultrasonically treating the mixture;
[0013] (3) adding the mixed solution after ultrasonic treatment in step (2) dropwise onto the surface of carbon paper on a heating table at 120° C. until the solution is completely evaporated and dried;
[0014] (4) heating the dried sample obtained in step (3) to 200-500° C. at 5-10° C. / min in an air atmosphere and keeping the temperature for 2-6 hours;
[0015] (5) Washing, ultrasonically removing impurities and drying the sample after the heat preservation treatment in step (4) to obtain catalyst M-Mn X Co 3- X O4, wherein M is a doping metal, 1≤X≤3, and X is a positive integer.
[0016] In some embodiments, the manganese-containing compound is at least one of manganese nitrate, manganese carbonate, manganese acetate, manganese chloride and manganese oxide, and the cobalt-containing compound is at least one of cobalt nitrate, cobalt carbonate, cobalt acetate, cobalt chloride and cobalt oxide.
[0017] In some embodiments, in step (1), the ultrasonic treatment temperature is 20-30° C., and the ultrasonic treatment time is 0.5-5 h.
[0018] In some embodiments, in step (2), the ultrasonic treatment temperature is 20-30° C., and the ultrasonic treatment time is 0.5-2 h.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The metal-doped spinel catalyst for light-driven water electrolysis provided by the present invention is a d-block metal-doped Mn X Co 3-X O4; M-Mn prepared by the present invention X Co 3-X O4 material has excellent acid corrosion resistance, high catalytic activity and long-lasting durability, and the photovoltaic-driven acidic water electrolysis achieved a light-to-hydrogen fuel conversion efficiency of more than 20%. In addition, the preparation process of the present invention is simple to operate, the reaction conditions are mild, and the industrialization cost of catalyst application is greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 The XRD spectrum of the Ti-MnCo2O4 material prepared in Example 1 of the present invention;
[0023] Figure 2 The LSV diagram of IrO2 acidic water oxidation of Ti-MnCo2O4 material prepared in Example 1 of the present invention;
[0024] Figure 3 The LSV diagram of acidic water oxidation of V-MnCo2O4 prepared in Example 2 of the present invention;
[0025] Figure 4 This is a durability diagram of Ti-CoMn2O4 prepared in Example 3 of the present invention when operating in an acidic medium;
[0026] Figure 5 This is a diagram of the light-to-hydrogen fuel conversion efficiency of the photovoltaic-driven acidic water electrolysis constructed with Ti-CoMn2O4 prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.
[0029] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.
[0030] Example 1
[0031] A method for preparing a metal-doped spinel catalyst for light-driven water electrolysis comprises the following steps:
[0032] Weigh 0.8mmol of hexahydrated cobalt nitrate, 0.4mmol of manganese chloride and 0.09mmol of 15% titanium trichloride solution (containing Ti 0.0279mmol) respectively, add them to a 2.0mL sample tube, then add 275μl of distilled water, and ultrasonically treat at 25℃ for 1 hour to obtain a uniform mixed solution. Then add 25μl of 5wt% Nafion solution, and ultrasonically treat at 25℃ for 0.5 hour to obtain a uniform mixed solution. The ultrasonically treated mixed solution is dripped onto the surface of carbon paper on a 120℃ heating table, and continuously heated until the solution is completely evaporated and dried. The evaporated and dried sample is heated to 300℃ at a rate of 5℃ / min in an air atmosphere, and heat-treated for 4 hours. After cooling to room temperature, take out the heat-treated sample, wash it, remove excess impurities by ultrasonication, and obtain Ti-MnCo2O4 after drying.
[0033] The XRD pattern of the prepared Ti-MnCo2O4 nano-electrocatalyst is shown in Figure 1 As shown, its X-ray diffraction data matches the PDF card #23-1237 (i.e., MnCo2O4) of the International Powder Diffraction Data Center, which proves that the prepared material is Ti-MnCo2O4.
[0034] The Ti-MnCo2O4 nano-electrocatalyst and IrO2 benchmark catalyst prepared above were used in the electrocatalytic anode water oxidation test. The amount of the benchmark catalyst was 2.0 mg, the test electrolyte was 0.1M HClO4, and the operating temperature was 40°C. The operating data results are shown in Figure 2 As shown, Ti-MnCo2O4 at 10mAcm -2 The current density of only about 220mV bias is required, while IrO2 requires about 270mV.
[0035] Example 2
[0036] A method for preparing a metal-doped spinel catalyst for light-driven water electrolysis comprises the following steps:
[0037] Weigh 0.8mmol hexahydrated cobalt nitrate, 0.4mmol manganese chloride and 0.09mmol vanadium trichloride solution (containing V0.0293mmol) with a mass concentration of 15% respectively, add them to a 2.0mL sample tube, then add 275μl of distilled water, and ultrasonically treat at 25℃ for 1 hour to obtain a uniform mixed solution. Then add 25μl 5wt% Nafion solution, and ultrasonically treat at 25℃ for 0.5 hour to obtain a uniform mixed solution. The ultrasonically treated mixed solution is dripped onto the surface of carbon paper on a 120℃ heating table, and continuously heated until the solution is completely evaporated and dried. The evaporated and dried sample is heated to 360℃ at a rate of 10℃ / min in an air atmosphere, and heat-treated for 3 hours. After cooling to room temperature, take out the heat-treated sample, wash it, remove excess impurities by ultrasonication, and dry it to obtain V-MnCo2O4.
[0038] The V-MnCo2O4 nano-electrocatalyst and IrO2 benchmark catalyst prepared above were used in the electrocatalytic anode water oxidation test. The amount of the benchmark catalyst was 2.0 mg, the test electrolyte was 0.1 M HClO4, and the operating temperature was 40°C. Figure 3 As shown, V-MnCo2O4 at 10mAcm -2 A current density of only about 255mV bias is required.
[0039] Example 3
[0040] A method for preparing a metal-doped spinel catalyst for light-driven water electrolysis comprises the following steps:
[0041] Weigh 0.4mmol of hexahydrated cobalt nitrate, 0.8mmol of manganese chloride and 0.09mmol of 15% titanium trichloride solution (containing Ti 0.0279mmol) respectively, add them to a 2.0mL sample tube, then add 275μl of distilled water, and ultrasonically treat at 25℃ for 1 hour to obtain a uniform mixed solution. Then add 25μl of 5wt% Nafion solution, and ultrasonically treat at 25℃ for 0.5 hour to obtain a uniform mixed solution. The ultrasonically treated mixed solution is dripped onto the surface of carbon paper on a 120℃ heating table, and continuously heated until the solution is completely evaporated and dried. The evaporated and dried sample is heated to 400℃ at a rate of 5℃ / min in an air atmosphere, and heat-treated for 2.5 hours. After cooling to room temperature, take out the heat-treated sample, wash it, remove excess impurities by ultrasonication, and obtain Ti-CoMn2O4 after drying.
[0042] The Ti-CoMn2O4 nano-electrocatalyst prepared above was subjected to anode water oxidation durability test in 0.1M HClO4 electrolyte at room temperature. Figure 4 As shown, at 10 mA cm -2 It can operate stably for more than 300 hours at a current density of 1.50 W with only slight performance degradation.
[0043] The Ti-CoMn2O4 nanocatalyst prepared above was coupled with PV to construct a photovoltaic-driven acidic water electrolysis system, such as Figure 5 As shown, the conversion efficiency of light to hydrogen fuel exceeds 20%.
[0044] Example 4
[0045] A method for preparing a metal-doped spinel catalyst for light-driven water electrolysis comprises the following steps:
[0046] Weigh 0.8mmol of hexahydrated cobalt nitrate, 0.4mmol of manganese chloride and 0.03mmol of 15% titanium trichloride solution (containing 0.0093mmol of Ti) respectively, add them to a 2.0mL sample tube, then add 275μl of distilled water, and ultrasonically treat at 25℃ for 1 hour to obtain a uniform mixed solution. Then add 25μl of 5wt% Nafion solution, and ultrasonically treat at 25℃ for 0.5 hour to obtain a uniform mixed solution. The ultrasonically treated mixed solution is dripped onto the surface of carbon paper on a 120℃ heating table, and continuously heated until the solution is completely evaporated and dried. The evaporated and dried sample is heated to 300℃ at a rate of 5℃ / min in an air atmosphere, and heat-treated for 4 hours. After cooling to room temperature, take out the heat-treated sample, wash it, remove excess impurities by ultrasonication, and obtain Ti-MnCo2O4 after drying.
[0047] The prepared Ti-MnCo2O4 nano-electrocatalyst and IrO2 benchmark catalyst were used in the electrocatalytic anode water oxidation test. The amount of the benchmark catalyst was 2.0 mg, the test electrolyte was 0.1 M HClO4, and the operating temperature was 40 °C. -2 The current density only requires a bias of about 242 mV, and at 10 mA cm -2 It can operate stably for more than 300 hours at a current density of 1.50 W with only slight performance degradation.
[0048] Example 5
[0049] A method for preparing a metal-doped spinel catalyst for light-driven water electrolysis comprises the following steps:
[0050] Weigh 0.8mmol of hexahydrated cobalt nitrate, 0.4mmol of manganese chloride and 0.13mmol of 15% titanium trichloride solution (containing 0.0403mmol of Ti) respectively, add them to a 2.0mL sample tube, then add 275μl of distilled water, and ultrasonically treat at 25℃ for 1 hour to obtain a uniform mixed solution. Then add 25μl of 5wt% Nafion solution, and ultrasonically treat at 25℃ for 0.5 hour to obtain a uniform mixed solution. The ultrasonically treated mixed solution is dripped onto the surface of carbon paper on a 120℃ heating table, and continuously heated until the solution is completely evaporated and dried. The evaporated and dried sample is heated to 300℃ at a rate of 5℃ / min in an air atmosphere, and heat-treated for 4 hours. After cooling to room temperature, take out the heat-treated sample, wash it, remove excess impurities by ultrasonication, and obtain Ti-MnCo2O4 after drying.
[0051] The prepared Ti-MnCo2O4 nano-electrocatalyst and IrO2 benchmark catalyst were used in the electrocatalytic anode water oxidation test. The amount of the benchmark catalyst was 2.0 mg, the test electrolyte was 0.1 M HClO4, and the operating temperature was 40 °C. -2 The current density only requires a bias of about 253 mV, and at 10 mA cm -2 It can operate stably for more than 300 hours at a current density of 1.50 W with only slight performance degradation.
[0052] Example 6
[0053] A method for preparing a metal-doped spinel catalyst for light-driven water electrolysis comprises the following steps:
[0054] Weigh 1.2mmol manganese chloride and 0.09mmol titanium trichloride solution (containing Ti0.0279mmol) with a mass concentration of 15% respectively, add them to a 2.0mL sample tube, then add 275μl of distilled water, and ultrasonically treat at 25℃ for 1 hour to obtain a uniform mixed solution. Then add 25μl of 5wt% Nafion solution, and ultrasonically treat at 25℃ for 0.5 hour to obtain a uniform mixed solution. The ultrasonically treated mixed solution is dripped onto the surface of carbon paper on a 120℃ heating table, and continuously heated until the solution is completely evaporated and dried. The evaporated and dried sample is heated to 300℃ at a rate of 5℃ / min in an air atmosphere, and heat-treated for 4 hours. After cooling to room temperature, take out the heat-treated sample, wash it, remove excess impurities by ultrasonication, and obtain Ti-Mn3O4 after drying.
[0055] The prepared Ti-Mn3O4 nano-electrocatalyst and IrO2 benchmark catalyst were used in the electrocatalytic anode water oxidation test. The amount of the benchmark catalyst was 2.0 mg, the test electrolyte was 0.1M HClO4, and the operating temperature was 40°C. -2 The current density only requires a bias of about 246 mV, and at 10 mA cm -2 It can operate stably for more than 300 hours at a current density of 1.50 W with only slight performance degradation.
[0056] Example 7
[0057] A method for preparing a metal-doped spinel catalyst for light-driven water electrolysis comprises the following steps:
[0058] Weigh 1.2mmol of cobalt nitrate hexahydrate and 0.09mmol of titanium trichloride solution with a mass concentration of 15% (containing Ti 0.0279mmol) respectively, add them to a 2.0mL sample tube, then add 275μl of distilled water, and ultrasonically treat at 25℃ for 1 hour to obtain a uniform mixed solution. Then add 25μl of 5wt% Nafion solution, and ultrasonically treat at 25℃ for 0.5 hour to obtain a uniform mixed solution. The ultrasonically treated mixed solution is dripped onto the surface of carbon paper on a 120℃ heating table, and continuously heated until the solution is completely evaporated and dried. The evaporated and dried sample is heated to 300℃ at a rate of 5℃ / min in an air atmosphere, and heat-treated for 4 hours. After cooling to room temperature, take out the heat-treated sample, wash it, remove excess impurities by ultrasonication, and obtain Ti-Co3O4 after drying.
[0059] The Ti-Co3O4 nano-electrocatalyst and IrO2 benchmark catalyst prepared above were used in the electrocatalytic anode water oxidation test. The amount of benchmark catalyst was 2.0 mg, the test electrolyte was 0.1M HClO4, and the operating temperature was 40°C.-2 The current density only requires a bias of about 243 mV, and at 10 mA cm -2 It can operate stably for more than 300 hours at a current density of 1.50 W with only slight performance degradation.
[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A metal-doped spinel catalyst for light-driven water electrolysis, characterized in that: The catalyst is based on spinel material and the doped metal is a d-zone transition metal.
2. The metal-doped spinel catalyst for light-driven water electrolysis according to claim 1, characterized in that: The spinel material includes at least one of MnCo2O4, CoMn2O4, Co3O4, and Mn3O4.
3. The metal-doped spinel catalyst for light-driven water electrolysis according to claim 1, characterized in that: The doping metal includes at least one of Ti, V, Nb and Ta.
4. The metal-doped spinel catalyst for light-driven water electrolysis according to claim 1, characterized in that: The molar ratio of the doping metal is 2.5%-10%.
5. The method for preparing the metal-doped spinel catalyst for light-driven water electrolysis according to any one of claims 1 to 4, characterized in that: The steps include: (1) mixing a spinel precursor compound and a doping metal compound to prepare an aqueous solution, and subjecting the mixture to ultrasonic treatment, wherein the spinel precursor compound comprises at least one of a manganese-containing compound and a cobalt-containing compound; (2) mixing the mixed solution after ultrasonic treatment in step (1) with the Nafion solution and then ultrasonically treating the mixture; (3) adding the mixed solution after ultrasonic treatment in step (2) dropwise onto the surface of carbon paper on a heating table at 120° C. until the solution is completely evaporated and dried; (4) heating the dried sample obtained in step (3) to 200-500° C. at 5-10° C. / min in an air atmosphere and keeping the temperature for 2-6 hours; (5) The sample after the heat preservation treatment in step (4) is washed, ultrasonically cleaned, and dried to obtain a catalyst.
6. The method for preparing a metal-doped spinel catalyst for light-driven water electrolysis according to claim 5, characterized in that: The manganese-containing compound is at least one of manganese nitrate, manganese carbonate, manganese acetate, manganese chloride and manganese oxide, and the cobalt-containing compound is at least one of cobalt nitrate, cobalt carbonate, cobalt acetate, cobalt chloride and cobalt oxide.
7. The method for preparing a metal-doped spinel catalyst for light-driven water electrolysis according to claim 5, characterized in that: In step (1), the ultrasonic treatment temperature is 20-30°C, and the ultrasonic treatment time is 0.5-5h.
8. The method for preparing a metal-doped spinel catalyst for light-driven water electrolysis according to claim 5, characterized in that: In step (2), the ultrasonic treatment temperature is 20-30°C, and the ultrasonic treatment time is 0.5-2h.